2008
DOI: 10.1523/jneurosci.5572-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of IP3Receptor-Dependent Ca2+Increases in Hippocampal Astrocytes Does Not Affect Baseline CA1 Pyramidal Neuron Synaptic Activity

Abstract: 2ϩ . Furthermore, neuronal G q -linked GPCR Ca 2ϩ increases remain intact, suggesting that IP 3 R2 does not play a major functional role in neuronal calcium store release or may not be expressed in neurons. Additionally, we show that lack of IP 3 R2 in the hippocampus does not affect baseline excitatory neuronal synaptic activity as measured by spontaneous EPSC recordings from CA1 pyramidal neurons. Whole-cell recordings of the tonic NMDA receptor-mediated current indicates that ambient glutamate levels are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
292
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(318 citation statements)
references
References 52 publications
23
292
1
2
Order By: Relevance
“…This does not necessarily imply that elegant experimental manipulations with astroglial Ca 2+ within a certain dynamic range by triggering certain cellular cascades should reproduce such effects (Agulhon et al, 2010; Fiacco et al, 2007; Petravicz et al, 2008) (see (Rusakov et al, 2014; Volterra et al, 2014) for discussion). In addition to the much debated astrocyte‐neuron exchange, Ca 2+ rises in astrocytes could also boost the expression level of glutamate transporters (Devaraju et al, 2013), re‐position mitochondria closer to glutamate transporters (Jackson et al, 2014; Ugbode et al, 2014), and regulate neuro‐metabolic coupling with neurons (Bernardinelli et al, 2004; Porras et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This does not necessarily imply that elegant experimental manipulations with astroglial Ca 2+ within a certain dynamic range by triggering certain cellular cascades should reproduce such effects (Agulhon et al, 2010; Fiacco et al, 2007; Petravicz et al, 2008) (see (Rusakov et al, 2014; Volterra et al, 2014) for discussion). In addition to the much debated astrocyte‐neuron exchange, Ca 2+ rises in astrocytes could also boost the expression level of glutamate transporters (Devaraju et al, 2013), re‐position mitochondria closer to glutamate transporters (Jackson et al, 2014; Ugbode et al, 2014), and regulate neuro‐metabolic coupling with neurons (Bernardinelli et al, 2004; Porras et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…We found that after an RB-induced photothrombosis, leakage of 2MeSADP across the blood-brain barrier elicited Ca 2 þ increases in astrocytes in control wild-type mice ( Figures 5A and 5B), but not in IP 3 R type2 knockout mice ( Figures 5C and 5D), consistent with the observations of Petravicz and coworkers. 21 The average peak amplitude of wild-type astrocytic Ca 2 þ responses within 50 mm of the clotted vessel was 0.76 ± 0.09 (DF/F, n ¼ 3 mice pooled from 51 cells). Direct measurements of the blood vessel diameter, before (32.3 ± 4.2, n ¼ 6) and after (31.8±5.1, n ¼ 7) astrocytic Ca 2 þ revealed no acute changes in the vasculature.…”
Section: P2y 1 R-enhanced Neuroprotection Correlates With Reversal Ofmentioning
confidence: 97%
“…IP 3 R type2 knockout mice were utilized, since their astrocytes lack spontaneous and G-protein coupled receptor mediated Ca 2 þ increases. 21 IP 3 R type2 knockout or control wild-type mice were prepared for in vivo cortical imaging using an open-skull preparation, which permitted cortical loading of the Ca 2 þ indicator dye Fluo-4 AM. 22 Mice were then treated and imaged as described above, including tail-vein injection of rose Bengal (RB) and 2MeSADP (100 mM).…”
Section: P2y 1 R-enhanced Neuroprotection Correlates With Reversal Ofmentioning
confidence: 99%
“…Previous studies have shown that inositol-1,4,5-trisphosphate (IP3)-dependent calcium release from the endoplasmic reticulum (ER) is important for astrocyte calcium signaling (Petravicz et al 2008;Nizar et al 2013;Takata et al 2013;Srinivasan et al 2015). We examined the involvement of this pathway in sensory stimulation-evoked astrocyte responses by expressing GCaMP6s in astrocytes from Ip3r2 -/-mice and wild-type (WT) littermate controls (Li et al 2005) and selecting sub-cellular ROIs in the same manner as previous experiments (manual selection for endfeet and somata ROIs and automated detection for processes).…”
Section: Astrocytes From Ip3r2 -/-Mice Also Respond To Sensory Stimulmentioning
confidence: 99%